Pharmacokinetics of Clivarin a new low molecular weight heparin in healthy volunteers - Andrassy, Konrad; Eschenfelder, Volker; Koderisch, Janti; Weber, E. (Thrombosis research, 1994)
The antithrombotic activity and pharmacokinetics of Clivarin®, a low molecular weight heparin was randomly studied in 10 healthy male volunteers. Doses of 20, 40, 60 and 80 anti F Xa U/kg BW were injected intravenously and subcutaneously in crossover fashion. The heparin concentrations were measured by inhibition of clotting assays (anti Ila and anti Xa activities using amidolytic assays and (dilute) thrombin time. The pharmacokinetic profile of Clivarin® is characterized by a linear relationship between dose and absorption, relatively low clearance and a long elimination half-life, and a high anti Xa/anti Ila ratio of 5.3.